Antimicrobial Resistance Profiles of E. coli Isolated From Pooled Samples of Sick, Farm, and Market Chickens in Nairobi County, Kenya - Tino A. Deng; Lilly C. Bebora; Mahacla O. Odongo; Gerald M. Muchemi; Samuel Karuki; Peter K. Gathumi (Veterinary Medicine International)
Bacterial antimicrobial resistance (AMR) is a global threat to both human and animal health. This is mainly because the same antimicrobial molecules are used for the treatment and prophylaxis of bacterial diseases in both cases, and about 60% of human pathogens are shared with animals. For effective control of AMR in any country, the current situation has to be established; this is done through surveillance exercises. In Kenya, there is scanty data on the prevailing AMR situation, especially in animals. This paper reports on AMR profiles of 54 E. coli strains isolated from chickens in a cross-sectional study, out of which 36/54 (72%) were from clinically ill chickens, 11/54 (22%) were from farm chickens, and 7/54 (9.7%) were from slaughtered chicken, respectively. All 54 isolates exhibited varying antimicrobial resistance profiles with the majority showing resistance to Ampicillin (85.22%), Tetracycline (66.7%), Co-trimoxazole (57.4%), and Streptomycin (40.7%). Very few isolates were resistant to Amoxicillin and Gentamicin (each at 3.7%), Ampicillin (11.1%), and Nalidixic acid (24.1%). A total of 44/54 (81.5%) showed multiple resistance to up to 6 antimicrobial agents. This information will augment current data on the AMR status of bacteria harbored by chickens in Kenya. It will also inform policymakers in their fight against AMR.